Description of a new Psalmopoeus Pocock, 1895 species (Araneae, Theraphosidae, Psalmopoeinae) from the Chocó region of Ecuador - Dupérré, Nadine; Tapia, Elicio (Zootaxa, 2024)
A new species of Theraphosidae, genus Psalmopoeus Pocock, 1895 is described from the Chocó region of Ecuador, Psalmopoeus pristirana n. sp. (male and female). The identity of the female of the recently described Psalmopoeus satanas Peñaherrera-R. & León-E., 2023 is discussed. Images of Psalmopoeus ecclesiasticus Pocock, 1903 are given for comparison and a distribution map of all Ecuadorian Psalmopoeus species is presented.